Beyond fears and hopes - Igor Sádaba; Javier de Rivera (Revista Teknokultura, 2012)
This issue of the Teknokultura Journal presents a selection of works in the social studies of digital technologies that draw an intellectual scenario in which the simplistic reactions of fear or hope, praise or rejection towards new technologies have been overcome. Critical studies of technology have begun to reach a certain point of maturity, going beyond apocalyptic and integrated stances, and developing certain perspectives that capture many of the complexities of this new techno-reality we are being thrown into. In order to avoid naturalizing the consolidation and integration of technological advances, it is important and urgent to supersede mythological views and naïve interpretations, and to focus our analysis on the historical and contingent relations between all social agents and social fields involved in these processes. In this sense, it is also essential to bear in mind our own responsibility as active social agents – whether individually, collectively or institutionally - in the development of technosocial change.